Clinical analysis of non-AIDS patients pathologically diagnosed with pulmonary cryptococcosis - Liu, Kaixiong; Ding, Haibo; Xu, Bing; You, Ruixiong; Xing, Zhen; Chen, Jianfeng; Lin, Qichang; Qu, Jieming (Journal of Thoracic Disease; Vol 8, No 10 (October 01, 2016): Journal of Thoracic Disease, 2016)
Background: Pulmonary cryptococcosis (PC) was not a rare infectious disease in non-AIDS patients. However, data on the immune status were lacking in southern China for comparative analysis of differences between immunocompromised and immunocompetent hosts. This study was to investigate the epidemiological, clinical, radiological, and treatment profiles for patients with PC. Methods: We performed a retrospective review of 88 patients diagnosed with tissue-confirmed PC who were not HIV-infected from 2003 to 2013. Results: Of 88 patients, 35(39.7%) were immunocompromised host. Fever and CNS symptom were significantly common in immunocompromised patients compared to immunocompetent patients (P=0.019 and P=0.036, respectively). The most frequent radiologic abnormalities were solitary or multiple pulmonary nodules, and masses or consolidations, and most lesions were located in the peripheral lung field. Cavitation and halo sign were significantly frequent in immunocompromised patients than in immunocompetent patients (P